Thank You, Akira Hayami! The Xavier Database of Historical Japan - Satomi Kurosu; Miyuki Takahashi; Hao Dong (Historical Life Course Studies)
This article introduces the Xavier database, one of the major sources for studying historical populations in Japan. The database consists of 162 years of annual observations for 28,105 individuals living in three villages and one town of the current Fukushima prefecture between 1708 and 1870. We review the extensive efforts of the founder of Japanese historical demography, Akira Hayami, and his group in collecting, transcribing, coding, and finally making local population registers into this database for demographic analysis. We discuss the studies that flourished domestically and internationally using the data in the last two decades, followed by the discussion of current and promising development.